1988
DOI: 10.1017/s0043174500074932
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Translocation, and Toxicity of Foliar-Applied Imazaquin in Yellow and Purple Nutsedge (Cyperus esculentusandC. rotundus)

Abstract: Imazaquin {2-[4,5-dihydro-4-methyl-4-(1-methylethyl)-5-oxo-1H-imidazol-2-yl]-3-quinolinecarboxylic acid} absorption, translocation, and toxicity were investigated in yellow nutsedge (Cyperus esculentusL. # CYPES) and purple nutsedge (C. rotundusL. # CYPRO) after foliar treatment. Imazaquin rates from 0.125 to 0.375 kg ai/ha were sprayed on nutsedge plants at the four-leaf stage. Compared to untreated plants, these rates reduced the main shoot growth of yellow nutsedge by 70 to 86% and that of purple nutsedge b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Norflurazon {4-chloro-5-(methylamino )-2-[3-(trifluoromethyl)phenyl]-3(2H)-pyridazinone} and pyrithiobac { 2-c h 10 ro-6-[( 4, 6-d i me thoxy -2 -py ri midinyl)thio]benzoic acid) in cotton (Gossypium hirsutum L.) and chlorimuron {ethyI2- [[[[4-chloro-6-methoxy-2pyrimidinyl)amino ]carbonyl]amino ]sulfonyl]benzoate }, imazaquin (2-[4,5-dihydro-4-methyl-4-(1-methylethyl)-5-oxo-1H-imadozol-2-yl]-3-quinolinecarboxylic acid}, imazamox (2-[ 4,5-dihydro-4-methyl-4-( I-methylethyl)-5-oxo-1H-imidazol-2-yl]-5-(methoxymethyl)-3pyridinecarboxylic acid}, and sulfentrazone {N-[2,4-dichloro-5-[4-( difluoromethy 1 )-4,5-dihydro-3-methy 1-5oxo-1H-l,2,4-triazol-l-yl]phenyl]methanesulfonamide} in soybean [Glycine max (L.) Merr.] provide various levels of purple nutsedge control (Anonymous 1998;Jordan 1996;Nandihalli and Bendixen 1988;Reddy and Bendixen 1988;Wilcut 1998;WSSA 1994WSSA , 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Norflurazon {4-chloro-5-(methylamino )-2-[3-(trifluoromethyl)phenyl]-3(2H)-pyridazinone} and pyrithiobac { 2-c h 10 ro-6-[( 4, 6-d i me thoxy -2 -py ri midinyl)thio]benzoic acid) in cotton (Gossypium hirsutum L.) and chlorimuron {ethyI2- [[[[4-chloro-6-methoxy-2pyrimidinyl)amino ]carbonyl]amino ]sulfonyl]benzoate }, imazaquin (2-[4,5-dihydro-4-methyl-4-(1-methylethyl)-5-oxo-1H-imadozol-2-yl]-3-quinolinecarboxylic acid}, imazamox (2-[ 4,5-dihydro-4-methyl-4-( I-methylethyl)-5-oxo-1H-imidazol-2-yl]-5-(methoxymethyl)-3pyridinecarboxylic acid}, and sulfentrazone {N-[2,4-dichloro-5-[4-( difluoromethy 1 )-4,5-dihydro-3-methy 1-5oxo-1H-l,2,4-triazol-l-yl]phenyl]methanesulfonamide} in soybean [Glycine max (L.) Merr.] provide various levels of purple nutsedge control (Anonymous 1998;Jordan 1996;Nandihalli and Bendixen 1988;Reddy and Bendixen 1988;Wilcut 1998;WSSA 1994WSSA , 1998.…”
Section: Introductionmentioning
confidence: 99%
“…In greenhouse studies using purple nutsedge grown in pots, significant reductions in shoot and root tuber growth and in shoot regrowth were obtained with foliar applications of rmazaquin { (t)-2-14,5-dihydro-4-methyl-4 -(1methy lethyl ) -5o x o -L H -rmrdazol-Z -yl I -3qui no linecarboxylic acid) (Derr and Wilcut 1993;Nandihalli and Bendixen 1988a), imazethapyr { (I)-2-14,5-dihydro-4 -methyl-4 -( 1methy I ethy I ) -5o x o -I Htmrdazol-2 -yll -5ethyl-3-pyridinecarbolilic acid) (Richburg et al 1993), AC 263,222 { ( t )-2-14,5 -dihydro -4-methyl-4-( 1methy lethy 1 ) -5o x o -I H -rmrdazol-Z -yI)-5me thy I -3p yri dinecarboxylic acid) (Richburg et al 1994), MON 12037 (Vencill et al 1995), and soil applications of chlorimuron (Reddy and Bendixen 1989). These results demonstrate that when applied to young, actively growing plants, excellent control was achieved and regrowth was prevented.…”
Section: Introductionmentioning
confidence: 99%
“…In greenhouse studies using purple nutsedge grown in pots, significant reductions in shoot and root tuber growth and in shoot regrowth were obtained with foliar applications of imazaquin {( ± )-2-[ 4,5-dihydro-4-methyl-4-( I-methylethyl)-5-oxo-lH-imidazol-2-yl]-3-quinolinecarboxylic acid) (Derr and Wilcut 1993;Nandihalli and Bendixen 1988a), imazethapyr (±)-2-[4,5-dihydro-4-methyl-4-( I-methylethyl)-5-oxo-1H-imidazol-2-yl]-5ethyl-3-pyridinecarbolilic acid) (Richburg et a1. 1993), AC 263,222 {(±)-2-[4,5-dihydro-4-methyl-4-(1-methy lethy 1)-5-oxo-l H -imidazol-2-y 1] -5-methy 1-3-pyridinecarboxylic acid} (Richburg et a1.…”
Section: Introductionmentioning
confidence: 99%
“…Fomesafen, chlorimuron, and imazaquin are new herbicides in the diphenyl ether, sul-fonylurea, and imidazolinone herbicide families, respectively. Although they are only registered for use in agronomic crops, they reportedly control yellow nutsedge (Nandihalli and Bendixen, 1988;Reddy and Bendixen, 1988;G. R. W., unpublished data).…”
mentioning
confidence: 99%
“…These results support those presented in Table 1, in which 100% control of yellow nutsedge was obtained from PPI and PRE applications of imazaquin and chlorimuron. Nandihalli and Bendixen (1988) reported that soil applications of imazaquin above the tubers (mimicking PPI and PRE applications) inhibited regrowth more than placement below the tuber.…”
mentioning
confidence: 99%